Inovasi Pemasaran dan Manajemen SDM Berkelanjutan dengan Pendekatan ABCD (Studi Kasus PT Berkah Tani Lestari Ponorogo) - Hamid Alwi Musarraf; Ahmad Kirom (Social Science Academic, 2025)
This service applies the ABCD (Asset-Based Community-driven Development) approach to develop marketing innovations and human resource management at PT Berkah Tani Lestari Ponorogo. The service was held from July 16 to August 28, 2025 at the Tani Lestari Blessing Garden, located in Njali Hamlet, Mrican Village, Jenangan District, Ponorogo Regency. ABCD is implemented by utilizing community assets in the form of agricultural land, local labor, farming experience, and existing marketing networks. These assets were identified and mobilized to design a marketing strategy for "BUMI Lestari" cashew fertilizer, develop chili harvest agro-tourism, and build a structured work management system. The purpose of this research is to design a marketing strategy for 'BUMI Lestari' cashmere fertilizer, develop agro-tourism innovations for chili harvesting to increase selling value, as well as build a structured plantation management system and marketing partnership model that strengthens farmers' bargaining positions. The methods used include in-depth interviews, participatory observations, and direct collaboration with farmers. The results of the service show that the implementation of ABCD increases community involvement, strengthens farmers' bargaining positions, increases the selling price of products by up to 50%, and creates better work discipline. These findings confirm the important role of local asset-based approaches in realizing sustainable agriculture.